The Roman mass: from early Christian origins to Tridentine reform - Lang, Uwe Michael (Cambridge University Press, 2022)
This volume offers a new, synthetic overview of the structure and ritual shape of the Roman Mass from its formative period in late antiquity to its post-Tridentine standarisation. Starting with the Last Supper and the origins of the Eucharist, Uwe Michael Lang constructs a narrative that explores the intense religious, social, and cultural transformations that shaped the Roman Mass. Lang unites classical liturgical history with insights from a variety of other disciplines that have drawn attention to the ritual performance and reception of the mass. He also presents liturgical developments within the broader historical and theological contexts that affected the celebration and experience of the sacramental rite that is still at the heart of Catholic Christianity. Aimed at scholars from a broad swathe of subjects, including religious studies, history, art history, literature, and music, Lang's volume serves as a comprehensive history of the Roman Mass over the course of a millenium.